OP0233 Genome-Wide Pathway Analysis Reveals that VEGF Genetic Pathway Is Associated with Oral Ulcers in Systemic Lupus Erythematosus. (15th July 2016) - Julià, A.; Carreira, P.; Blanco, R.; Martínez Taboada, V.; Carreño Pérez, L.; Pérez-Venegas, J.; Olivé, À.; Andreu, J.L.; Aguirre Zamorano, M.; Vela, P.; Nolla, J.M.; Marenco de la Fuente, J.L.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is a genetically complex rheumatic disease with heterogeneous clinical manifestations. Recent studies have suggested the existence of a genetic basis for the diverse SLE clinical phenotypes. Also, there is increasing evidence indicating that a substantial part of the genetic variation associated with complex diseases is explained by small-effect genes from common genetic pathways. Objectives: The objective of the present study was to identify new genetic variation associated with SLE phenotypes using a genome-wide association study at the pathway level. Methods: A total of 598, 258 SNPs were genotyped in a discovery cohort of n=482 SLE patients of southern European ancestry using the Illumina platform Quad610. After quality control analysis, including ancestry estimation using principal-component analysis, genome-wide pathway analysis was performed. A total of 14 clinically relevant SLE phenotypes were tested for association with n>700 reference genetic pathways. Significantly associated pathways (corrected P-value <0.05) were subsequently tested for validation in an independent cohort of n=425 SLE patients from the same ancestry. Both discovery and validation cohort patients were Caucasian European and from Spanish origin, and were recruited by rheumatology departments from n=15 Spanish university hospitals. The validated genetic pathways were functionally characterized using in silico analysis on cell types of relevance in SLE pathogenesis. Results: In the discovery stage, two genetic pathways were significantly associated with the presence of oral ulcers and antinuclear antibodies in SLE ( P FDR <0.05). In the replication stage, we validated the association between oral ulcers and vascular endothelial growth factor ( VEGF ) genetic pathway ( P =1.3e-2). Analyzing the transcriptional effect of the topical immunotherapies used for the treatment of oral ulcers in SLE, we found a significant differential expression of VEGF pathway genes ( P <0.05). Conclusions: In this work we have performed the first genome-wide association study for clinically relevant SLE phenotype using a pathway-based approach. With this new approach, we have identified and validated the association of VEGF genetic pathway with oral ulcers in SLE. These findings represent an important step towards the characterization of the genetic basis of phenotype heterogeneity in SLE. Disclosure of Interest: None declared